2005
DOI: 10.1007/s11120-005-5302-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-optically Induced Reorganizations in the Main Light Harvesting Antenna of Plants. II. Indications for the Role of LHCII-only Macrodomains in Thylakoids

Abstract: We have investigated the circular dichroism spectral transients associated with the light-induced reversible reorganizations in chirally organized macrodomains of pea thylakoid membranes and loosely stacked lamellar aggregates of the main chlorophyll a/b light harvesting complexes (LHCII) isolated from the same membranes. These reorganizations have earlier been assigned to originate from a thermo-optic effect. According to the thermo-optic mechanism, fast local thermal transients due to dissipation of the exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…It is unclear and cannot be discriminated based on the presently available data, if this partial disassociation of LHCII from PSII occurs only at the level of supercomplexes, or involves or rather preferentially occurs in the LHCII-only domains (Dekker and Boekema 2005). Based on transient CD spectra, it has been argued earlier (Holm et al 2005) that LHCII-only domains are more readily amenable for reorganizations. Their direct involvement in regular processes is more plausible than the involvement of LHCII-PSII supercomplexes.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear and cannot be discriminated based on the presently available data, if this partial disassociation of LHCII from PSII occurs only at the level of supercomplexes, or involves or rather preferentially occurs in the LHCII-only domains (Dekker and Boekema 2005). Based on transient CD spectra, it has been argued earlier (Holm et al 2005) that LHCII-only domains are more readily amenable for reorganizations. Their direct involvement in regular processes is more plausible than the involvement of LHCII-PSII supercomplexes.…”
Section: Resultsmentioning
confidence: 99%
“…An important role of light-induced LHCII reorganization in photoprotection against light-induced damage has emerged from several studies, both in vivo and in vitro (Barzda et al, 1996;Dobrikova et al, 2003;Cseh et al, 2005;Holm et al, 2005;Gruszecki et al, 2009b;Johnson et al, 2011). Most of these data suggest that the primary site of light-induced reorganizations is on the outer loop segments of LHCII, affecting the phosphorylation (Zer et al, 1999), the cation binding sites (Cseh et al, 2000;Garab and Mustardy, 2000), and the ability of stacking and lateral reorganizations (Dobrikova et al, 2003;Gruszecki et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Black and white horizontal bars indicate dark and light periods, respectively; the schematic illustration shows that upon illumination of the sample with excess light, the long-range order of the complexes is perturbed (panel a ). Very similar kinetics are displayed by all main psi-type CD bands, indicating an overall reorganization of the chiral macrodomains in the grana (Garab et al 1988 ;Holm et al 2005 ). Panel b is reproduced from Garab ( 2014 ).…”
Section: A Involvement Of Structural Changes In Light-adaptation Mechmentioning
confidence: 67%
“…A large fraction of LHCII trimers are only loosely associated with the PS II supercomplex or are found in LHCII-only domains (Boekema et al 2000 ), and these readily detach from PS II as suggested by Holm et al ( 2005 ). Light-induced detachment of the phycobilisome antenna has also been observed in cyanobacteria under conditions that trigger NPQ (Stoitchkova et al 2007 ).…”
Section: Functional Domain Sizes and The Effective Radii Of Quenchersmentioning
confidence: 99%